Instrumentelle Gang- und Bewegungsanalyse bei muskuloskelettalen Erkrankungen - Sander, Klaus; Wolf, Sebastian Immanuel (Der Orthopäde, 2012)
Instrumented 3-dimensional gait analysis is increasingly being used for the evaluation of movement disorders in orthopedic and neurological musculoskeletal diseases. Due to the high reliability of the measurements the procedures are appropriate for diagnostic purposes as well as for outcome assessment after conservative or surgical interventions. Contrary to conventional clinical assessments gait analysis parameters are able to demonstrate a normal physiological gait pattern that can be achieved with improved kinematic and kinetic parameters. For a suitable application in clinically relevant problems the limitations of the procedures should be taken into account. Due to the high instrumental involvement combined with time and cost expenditure instrumented gait analysis will probably not develop to a clinical routine procedure. Nevertheless, an excellent set of information for answering clinical questions is provided. The present contribution presents selected measurement procedures and technologies and illustrates the wide variety of possibilities with the use of selected clinical examples.